A Review on Medicinal Plant of Glycyrrhiza glabra L. - M Khanahmadi M; H Naghdi Badi; S Akhondzadeh; F Khalighi - Sigaroodi; A Mehrafarin; S Shahriari; R Hajiaghaee (Institue of Medicinal Plants, ACECR, 2013)
Glycyrrhiza glabra L (Licorice) as native and pasture medicinal plant has most important export rule. Glycyrrhizic acid (GA) or Glycyrrhizin as a main active component of licorice root and rhizomes, is a triterpenoid saponin claimed to be up to 30-50 times sweeter than sucrose and to be used in pharmaceuticals, food and tobacco industry. Licorice root is a traditional medicine used mainly for the treatment of peptic ulcer, hepatitis C, and pulmonary and skin diseases, although clinical and experimental studies suggest that it has several other useful pharmacological properties such as antiinflammatory, antiviral, antimicrobial, antioxidative, anticancer activities, immunomodulatory, hepatoprotective and cardioprotective effects. A large number of components have been isolated from licorice, including triterpene saponins, flavonoids, isoflavonoids and chalcones, with glycyrrhizic acid normally being considered to be the main biologically active component. Understanding of the limitations and challenges in the medicinal plant are need for planning principles for development activities and conservation in this field.In this review summarizes the phytochemical, pharmacological and pharmacokinetics data, together with the clinical as one of the most important herbs in exports and adverse effects of licorice.